Other Solitudes: Canadian Multicultural Fictions - Hutcheon, Linda and Richmond, Marion (Toronto Oxford University Press, 1990)
This ground-breaking collection presents eighteen stories focusing on the immigrant experience, racism, and ethnic diversity in Canada, each one followed by an interview with its author.
Keywords: Fiction